Modelling aspects and risk analysis for road vehicles under non-stationary wind excitation. (24th November 2020) - Zhang, Xiaoyu; Proppe, Carsten
Strong crosswinds have a great influence on the stability of road vehicles. At exposed locations (e.g. embankments, long bridges), the topographical features may magnify the wind effects and thus cause accidents. In order to evaluate the accident risk of road vehicles in a more realistic way, the model for the wind-vehicle system has to take the non-stationary characteristics of natural wind into account and specific vehicle models for different vehicle types have to be developed. This paper details the mathematical model and physical scenario of road vehicles running under strong crosswinds. Possible road vehicle accidents due to excessive sideslip, yaw rotation and overturning are taken into account. In order to quantify the accident risk under strong crosswind, failure probabilities for different types of road vehicles are computed and analysed.